The Effect of Reciprocal Teaching on Developing the Reading Comprehension and Reading Strategies of Eleventh Grade EFL Students - Oraib Ramadan; Anwar Hussein Abdel Razeq (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: Reading is a critical skill that English language learners should learn effectively. The present study investigated the effect of Reciprocal Teaching (RT) method on developing English language learners reading comprehension skills and reading strategies.   Methods: The participants in this study were 165 11th grade female students, distributed into two groups: (Experimental = 84 students) and (Control = 81 students). Four instruments were used to collect the data: a pre/post-test in reading comprehension, five unit tests, a questionnaire and teacher's observation.  Data collected analyzed quantitatively and qualitatively.  Quantitatively, the independent sample T test was used to compare the means of the experimental and control groups in the pre/post-test and the unit tests.  The η 2 - Eta square was applied to the unit tests' results to examine the effect size of using RT. Descriptive statistical analysis was used to calculate the means, standard deviations and percentages of eighteen strategic reading practices.  Qualitative data was analysed used the Thematic analysis qualitative method.  Results: Data analysis showed that the experimental group outperformed the control group in the pre-post-test, unit tests and use of RT reading strategies. However, despite the fact that the experimental group outperformed its counterparts in the control group in the posttests, the calculation of their test results reveals that their performance wasn't great (M=11.42).  Conclusions: Recommendations and implications of using RT method in teaching reading comprehension were advanced and discussed.